Seed dispersal by wind: towards a conceptual framework of seed abscission and its contribution to long‐distance dispersal. (5th June 2013) - Pazos, Gustavo E.; Greene, David F.; Katul, Gabriel; Bertiller, Mónica B.; Soons, Merel B.; Jongejans, Eelke
Summary Diaspore abscission determines many aspects of seed dispersal by wind. While there is yet no complete mechanistic framework for understanding abscission by wind, empirical studies to date have suggested that abscission generally (i) occurs above some threshold wind speed and (ii) depends on the drag force generated by the wind. We revisit these findings and formulate two alternative hypotheses for abscission mechanisms based on a simple model of a forced harmonic oscillator: large diaspore displacement [through a maximum deflection threshold, (MDT)] and material fatigue [through a maximum cumulative stress threshold (MCST)]. We use simulations of abscission events based on these hypotheses and experiments on diaspore abscission of three Patagonian grasses and a cosmopolitan herb to test the performance of two abscission functions differing in whether they have a threshold wind speed for abscission. We also quantify the effects of non‐random diaspore abscission on dispersal distances using a well‐tested model for seed dispersal by wind. Both the MDT and MCST hypotheses appear realistic and indicate that while the instantaneous wind speed determines abscission, the history of wind speeds experienced prior to the detachment from the plant also plays a role. An evaluation of abscission functions against simulated and experimental abscission data shows that while the presence of a threshold wind speed in theory appears unrealistic, in practice a threshold may appear to exist in high‐wind‐speed environments where all diaspores are blown off the plant before the abscission layer can develop sufficiently to break during lower wind speeds. Under non‐random diaspore abscission, high‐wind‐speed events during otherwise calm periods increase long‐distance dispersal (LDD), thereby decreasing differences in dispersal distances between low‐ and high‐wind‐speed environments. Synthesis. We formulated two realistic mechanisms of diaspore abscission by applying concepts from materials science: large diaspore displacement and material fatigue. These reveal that the ambient wind speed 'history' experienced by a diaspore plays an important role in the timing of abscission and in the distance travelled, without any thresholds, and that the effect of the diaspore–wind interaction on LDD varies between environments with different wind speed regimes.